Structural and biophysical characteristics of human skin in maintaining proper epidermal barrier function - Boer, Magdalena; Duchnik, Ewa; Maleszka, Romuald; Marchlewicz, Mariola (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
The complex structure of human skin and its physicochemical properties turn it into an efficient outermost defence line against exogenous factors, and help maintain homeostasis of the human body. This role is played by the epidermal barrier with its major part – stratum corneum. The condition of the epidermal barrier depends on individual and environmental factors. The most important biophysical parameters characterizing the status of this barrier are the skin pH, epidermal hydration, transepidermal water loss and sebum excretion. The knowledge of biophysical skin processes may be useful for the implementation of prophylactic actions whose aim is to restore the barrier function.